2014
DOI: 10.1371/journal.pone.0096168
|View full text |Cite|
|
Sign up to set email alerts
|

Glucose Deprivation Induces G2/M Transition-Arrest and Cell Death in N-GlcNAc2-Modified Protein-Producing Renal Carcinoma Cells

Abstract: Some cancer cells can survive under glucose deprivation within the microenvironment of a tumor. Recently, we reported that N-linked (β-N-acetylglucosamine)2 [N-GlcNAc2]-modified proteins induce G2/M arrest and cell death under glucose deprivation. Here, we investigated whether such a response to glucose deprivation contributes to the survival of renal cell carcinomas, which are sensitive to nutritional stress. Specifically, we analyzed seven renal carcinoma cell lines. Four of these cell lines produced N-GlcNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 17 publications
2
28
0
1
Order By: Relevance
“…Recent in vitro and in vivo studies have shown that there are differential responses of cancer cells to glucose deprivation under different genetic and epigenetic background, indicating that metabolic profiles of tumors are likely dependent on both the genotype and tissue of origin [17, 18]. The restriction of glucose induced G1 phase arrest and apoptosis in breast, leukemia, prostate and lung cancer cells[15, 1821], while N-GlcNAc2-modified protein-producing renal carcinoma and bladder cancer cells arrested in G2/M-phase alone, with the changes triggered by glucose deprivation[22, 23]. In this study, we examined the changes in cell cycle and apoptosis in two endometrial cancer cell lines treated with different concentrations of glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vitro and in vivo studies have shown that there are differential responses of cancer cells to glucose deprivation under different genetic and epigenetic background, indicating that metabolic profiles of tumors are likely dependent on both the genotype and tissue of origin [17, 18]. The restriction of glucose induced G1 phase arrest and apoptosis in breast, leukemia, prostate and lung cancer cells[15, 1821], while N-GlcNAc2-modified protein-producing renal carcinoma and bladder cancer cells arrested in G2/M-phase alone, with the changes triggered by glucose deprivation[22, 23]. In this study, we examined the changes in cell cycle and apoptosis in two endometrial cancer cell lines treated with different concentrations of glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Some cancer cells increase their survival capacity under conditions of glucose deprivation [15, 16] by circumventing apoptotic signals. Indeed, CSCs displayed remarkably higher viability than did non-CSCs, which rapidly underwent apoptotic cell death in glucose deprivation [14] (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…However, cancer cells expressing highly SOD2 can survive in a nutritionally-depleted environment via preserving mitochondrial function and preventing ROS accumulation [22]. This helps to maintain the dormant character in RCC development [8,9]. It has been previously demonstrated that inhibitors targeting mitochondrial oxidative phosphorylation such as biguanides induce death of RCC cells and may become therapeutic options to overcome the disastrous consequences of SOD2abundance in RCC cells [9].…”
Section: Discussionmentioning
confidence: 99%